17 carnations : the royals, the Nazis, and the biggest cover-up in history - Morton, Andrew, 1953- (New York : Grand Central Publishing, 2015)
Examines the Duke and Duchess of Windsor's relationship with Germany and possible Nazi sympathies, a German plot to make him puppet king of a defeated England, and efforts by the British and American governments to conceal the evidence.
Includes bibliographical references and index.
Keywords: Windsor, Edward, -- Duke of, -- 1894-1972 -- Political and social views; Windsor, Wallis Warfield, -- Duchess of, -- 1896-1986; Hitler, Adolf, -- 1889-1945 -- Influence; Windsor, Edward, -- Duke of, -- 1894-1972.; Windsor, Wallis Warfield, -- Duchess of, -- 1896-1986; Hitler, Adolf, -- 1889-1945 -- Influence; National socialism; World War, 1939-1945 -- Great Britain; National socialism; World War, 1939-1945 -- Great Britain; Germany -- Politics and government -- 1933-1945.; Great Britain -- Politics and government -- 1936-1945.; Great Britain -- Kings and rulers -- Biography; Germany -- Politics and government; Great Britain -- Politics and government; Great Britain -- Kings and rulers -- Biography; Biographies